2019
DOI: 10.1001/jamanetworkopen.2019.1634
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medicare Spending With Subspecialty Consultation for Elderly Hospitalized Adults

Abstract: Key Points Question Does inpatient consultative care by medical subspecialists represent a potential opportunity for cost savings during an episode of hospitalization for nonsurgical conditions? Findings In this cross-sectional study of 735 627 hospital discharges among Medicare beneficiaries 65 years or older extrapolated to the population of Medicare fee-for-service beneficiaries, substantial variation in Medicare payments for medicine subspecialty consul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Finally, subspecialty consults, although often ordered in pursuit of a better understanding of risk, almost invariably lead to further testing and increased cost. 16,17 Clearer communication from providers regarding expectations and a stepwise tiered approach from a consultant may lead to more high-value consultant recommendations.…”
Section: Management Of Incidental Findings and The Cascade Effectmentioning
confidence: 99%
“…Finally, subspecialty consults, although often ordered in pursuit of a better understanding of risk, almost invariably lead to further testing and increased cost. 16,17 Clearer communication from providers regarding expectations and a stepwise tiered approach from a consultant may lead to more high-value consultant recommendations.…”
Section: Management Of Incidental Findings and The Cascade Effectmentioning
confidence: 99%
“…9 Studies of adult patients suggest significant subjectivity and variability in the extent of consultation utilization within and across hospitals. 2,5 While consultation practice patterns in adult populations have been characterized, 2,5,[9][10][11] our understanding of how and why pediatric hospitalists utilize consultations is limited. One descriptive study 12 found highly variable consultation utilization in 200 hospitalized children with uncertain diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“… 1 A separate study of 736 000 admissions of Medicare patients found subspecialty consultative care accounted for $1.3 billion of Medicare spending in 2014. 2 Given the ubiquity and expense of inpatient consultations, research has focused heavily on assessing variation in consultation use 1 , 3 , 4 , 5 and association with patient-level outcomes. 6 , 7 , 8 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…1 A separate study of 736 000 admissions of Medicare patients found subspecialty consultative care accounted for $1.3 billion of Medicare spending in 2014. 2 Given the ubiquity and expense of inpatient consultations, research has focused heavily on assessing variation in consultation use 1,[3][4][5] and association with patient-level outcomes. [6][7][8][9][10] A third research area centers on assessing communication among consultation stakeholders [11][12][13][14][15][16][17] and identifying factors that influence consultation "effectiveness."…”
Section: Introductionmentioning
confidence: 99%